2022
DOI: 10.1073/pnas.2024508119
|View full text |Cite
|
Sign up to set email alerts
|

Executioner caspases 3 and 7 are dispensable for intestinal epithelium turnover and homeostasis at steady state

Abstract: Apoptosis is widely believed to be crucial for epithelial cell death and shedding in the intestine, thereby shaping the overall architecture of the gastrointestinal tract, but also regulating tolerance induction, pinpointing a role of apoptosis intestinal epithelial cell (IEC) turnover and maintenance of barrier function, and in maintaining immune homeostasis. To experimentally address this concept, we generated IEC-specific knockout mice that lack both executioner caspase-3 and caspase-7 (Casp3/7ΔIEC), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Another related work by Farzaneh Ghazavia et al recently reported that caspase-3 and caspase-7 are dispensable for IEC turnover and homeostasis at a steady state. 5 Considering the results from Kengo Nozaki et al together, we can conclude that caspase-7 exerts the function of pore repair in pathological condition of IECs, but is redundant in the physiological condition of IECs. When working as an executioner of apoptosis, the pore repair function of caspase-7 seems to be shut down by some unknown mechanism.…”
mentioning
confidence: 85%
“…Another related work by Farzaneh Ghazavia et al recently reported that caspase-3 and caspase-7 are dispensable for IEC turnover and homeostasis at a steady state. 5 Considering the results from Kengo Nozaki et al together, we can conclude that caspase-7 exerts the function of pore repair in pathological condition of IECs, but is redundant in the physiological condition of IECs. When working as an executioner of apoptosis, the pore repair function of caspase-7 seems to be shut down by some unknown mechanism.…”
mentioning
confidence: 85%
“…Moreover, the clearance of Casp9 −/− thymocytes seems to occur in a caspase-independent fashion [1310]. In the same line, although apoptosis is widely believed to be crucial for epithelial cell death and shedding in the intestine, during steady state, executioner CASP3 and CASP7 are dispensable for intestinal epithelial cell turnover at the top of intestinal villi, intestinal tissue dynamics, microbiome, and immune cell composition, suggesting high redundancy in non-challenged conditions [464]. Apparently at odds with these observations, Casp3 −/− mice were reported to have abnormally increased numbers of splenic B cells manifesting increased proliferative capacity [1311], as well as a dysregulated activity in bone marrow stromal stem cells that attenuated osteogenic differentiation [1312].…”
Section: Box 4 Impact Of the Apoptosome And Apoptotic Caspases On Healthmentioning
confidence: 99%
“…In this context, it is interesting to note that CASP3-or CASP7-deficient mice display an altered gut microbiome [463], which may play a hitherto unexplored role in multiple autoimmune and inflammatory disorders beyond intestinal conditions. However, it has recently been found that under steady state conditions the absence of CASP3 and CASP7 in the intestinal epithelial cells apparently neither affects the microbiome nor causes spontaneous inflammation, suggesting that apoptosis may be dispensable for intestinal epithelium turnover and homeostasis at baseline [464].…”
Section: Autoimmune and Inflammatory Diseasesmentioning
confidence: 99%